Combining trade and sustainability? The Free Trade Agreement between the EU and Vietnam - Bernhard Tröster; Jan Grumiller; Hannes Grohs; Werner Raza; Cornelia Staritz; Rudi von Arnim (Austrian Foundation for Development Research (ÖFSE), 2019)
The European Union (EU) promotes the Free Trade Agreement with Vietnam (EVFTA) as an important milestone of its trade agenda. The agreement, whose part with EU-only issues is supposed to be ratified in 2019, is the most comprehensive one that the EU has concluded with a developing country so far, including an ambitious sustainability chapter. The reciprocal liberalization of tariffs and quotas will benefit important Vietnamese export sectors such as textiles, apparel, and footwear. On the other side, agricultural and industrial sectors in Vietnam might face increased import competition. Other provisions in the agreement such as the adoption of international or EU standards might be associated with adjustment costs. Thus, it will be crucial for Vietnam to promote its export sectors with pro-active upgrading policies. Further, the provisions in the sustainability chapter will have to demonstrate that increased trade and investment are compatible with labour and environmental protection. Both issues require substantive support by the EU.
Keywords: 330